Diagnostic and Therapeutic Approaches of Orbital Inflammatory Disease: A Systematic Review - Rashid, Riffat; Sultana, Sadia; Afzal, Farzana; Kadir, Syeed Mehbub Ul (Journal of National Institute of Ophthalmology, 2025)
Background: Orbital inflammatory disease (OID) is a group of disorders characterized by in-flammation in the orbit, which can affect various orbital structures, including the extraocular muscles, lacrimal glands, and orbital fat. One specific subset, pure orbital inflammation, is char-acterized by isolated inflammatory processes within the orbital tissues without the involvement of other systemic or regional disorders. The condition typically presents with symptoms such as pain, proptosis, and diplopia. Early diagnosis and appropriate management are crucial to pre-venting permanent damage to the orbit and maintaining visual function. This review assesses the diagnostic and therapeutic approaches to pure orbital inflammation. The review found that pure orbital inflammation is primarily treated with corticosteroids, which remain the first-line therapy. Relapses may be occured after complete resolution with appropriate steroid therapy. Immuno-suppressive agents are often used to improve outcomes in cases of steroid resistance or relapse. Additionally, imaging techniques such as CT and MRI are playing a key role in diagnosing the condition by identifying the extent of inflammation. In severe cases, biologic agents, radiothera-py, or surgical intervention may be required to prevent further orbital damage or to decompress the orbit in cases of significant proptosis. Orbital inflammatory disease is a treatable but poten-tially recurrent condition that requires careful clinical management. J.Natl.Inst.Ophthalmol. 2023; 6(2):73-82